If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying tan(x + 15) = cot(2x + -30) Reorder the terms: ant(15 + x) = cot(2x + -30) (15 * ant + x * ant) = cot(2x + -30) (15ant + antx) = cot(2x + -30) Reorder the terms: 15ant + antx = cot(-30 + 2x) 15ant + antx = (-30 * cot + 2x * cot) 15ant + antx = (-30cot + 2cotx) Solving 15ant + antx = -30cot + 2cotx Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Reorder the terms: 15ant + antx + 30cot + -2cotx = -30cot + 30cot + 2cotx + -2cotx Combine like terms: -30cot + 30cot = 0 15ant + antx + 30cot + -2cotx = 0 + 2cotx + -2cotx 15ant + antx + 30cot + -2cotx = 2cotx + -2cotx Combine like terms: 2cotx + -2cotx = 0 15ant + antx + 30cot + -2cotx = 0 Factor out the Greatest Common Factor (GCF), 't'. t(15an + anx + 30co + -2cox) = 0Subproblem 1
Set the factor 't' equal to zero and attempt to solve: Simplifying t = 0 Solving t = 0 Move all terms containing a to the left, all other terms to the right. Add '-1t' to each side of the equation. t + -1t = 0 + -1t Remove the zero: 0 = -1t Simplifying 0 = -1t The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(15an + anx + 30co + -2cox)' equal to zero and attempt to solve: Simplifying 15an + anx + 30co + -2cox = 0 Solving 15an + anx + 30co + -2cox = 0 Move all terms containing a to the left, all other terms to the right. Add '-30co' to each side of the equation. 15an + anx + 30co + -30co + -2cox = 0 + -30co Combine like terms: 30co + -30co = 0 15an + anx + 0 + -2cox = 0 + -30co 15an + anx + -2cox = 0 + -30co Remove the zero: 15an + anx + -2cox = -30co Add '2cox' to each side of the equation. 15an + anx + -2cox + 2cox = -30co + 2cox Combine like terms: -2cox + 2cox = 0 15an + anx + 0 = -30co + 2cox 15an + anx = -30co + 2cox The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 6x^4-x^3-x^2= | | 7.61n+3.21=-2.45n+5.02 | | 7x-y=15 | | x^5*x^4=ax^2 | | x+5y=21 | | 3b-2(b-5)=4+2b | | 6n^4+20n^3+14n^2=0 | | y(x-7)-3(x-7)= | | 0.12x+3-0.8x=0.22-0.6 | | y^4+3y^2-1=0 | | 2(4)-5y=11 | | -68x=-41 | | 9-(-21)+10= | | 5(-4.4)-27= | | 3=3-6z-4z | | 12x+3-80x=22-60 | | 8x-4x=-28 | | Y/6-2=2 | | 5y=25-15x | | 15y=25-5x | | 14/33*3/4= | | y+x+(15z)x=9 | | y=x^2+15z | | 2(7)-3(-2)= | | 5/6m=7/8 | | -1.3x=13 | | x/2=9.4 | | 7x=3x-6+2x | | 11x^2+8x+14=0 | | 75(x-2)+2x=50 | | 6x-30y=0 | | 6x+9x=15-19 |